Outflow cannula alignment in continuous flow left ventricular devices is associated with stroke. Issue 4 (April 2023) - Kassi, Mahwash; Agrawal, Tanushree; Xu, Jiaqiong; Marcos-Abdala, Hernan Gerardo; Araujo-Gutierrez, Raquel; Macgillivray, Thomas; Suarez, Erik E; Yousefzai, Rayan; Fida, Nadia; Kim, Ju H; Hussain, Imad; Guha, Ashrith; et al.
We sought to evaluate whether differences in left ventricular assist device (LVAD) canula alignment are associated with stroke. There is a paucity of clinical data on contribution of LVAD canulae alignment to strokes. We conducted a retrospective analysis of patients who underwent LVAD implantation at Houston Methodist hospital from 2011 to 2016 and included those who had undergone cardiac computed tomography (CT) with contrast. LVAD graft alignment using X-ray, echocardiography, and cardiac CT was evaluated. The primary outcome was stroke within 1 year of LVAD implantation. Of the 101 patients that underwent LVAD Implantation and cardiac CT scan during the study period, 78 met inclusion criteria. The primary outcome occurred in 12 (15.4%) patients with a median time to stroke of 77 days (interquartile range: 42–132 days). Of these, 10 patients had an ischemic and two had hemorrhagic strokes. The predominant device type was Heart Mate II (94.8%). Patients with LVAD outflow cannula to aortic angle lesser than 37.5° and those with outflow graft diameter of anastomosis less than 1.5 cm (assessed by cardiac CT) had significantly higher stroke risk ( p  < 0.001 and p  = 0.01 respectively). In HMII patients, a lower LVAD speed at the time of CT scan was associated with stroke. Further studies are needed to identify optimal outflow graft configuration to mitigate stroke risk.